FGF9 is a downstream target of SRY and sufficient to determine male sex fate in ex vivo XX gonad culture. Issue 6 (4th September 2020) - Li, Yi-Han; Chen, Tsung-Ming; Huang, Bu-Miin; Yang, Shang-Hsun; Wu, Chia-Ching; Lin, Yung-Ming; Chuang, Jih-Ing; Tsai, Shaw-Jenq; Sun, H Sunny
Abstract: Fibroblast growth factor 9 (FGF9) is an autocrine/paracrine growth factor that plays critical roles in embryonic and organ developments and is involved in diverse physiological events. Loss of function of FGF9 exhibits male-to-female sex reversal in the transgenic mouse model and gain of FGF9 copy number was found in human 46, XX sex reversal patient with disorders of sex development. These results suggested that FGF9 plays a vital role in male sex development. Nevertheless, how FGF9/Fgf9 expression is regulated during testis determination remains unclear. In this study, we demonstrated that human and mouse SRY bind to −833 to −821 of human FGF9 and −1010 to −998 of mouse Fgf9, respectively, and control FGF9/Fgf9 mRNA expression. Interestingly, we showed that mouse SRY cooperates with SF1 to regulate Fgf9 expression, whereas human SRY-mediated FGF9 expression is SF1 independent. Furthermore, using an ex vivo gonadal culture system, we showed that FGF9 expression is sufficient to switch cell fate from female to male sex development in 12–16 tail somite XX mouse gonads. Taken together, our findings provide evidence to support the SRY-dependent, fate-determining role of FGF9 in male sex development. Abstract : Summary Sentence FGF9 shows a fate-determining role within 6-h time windows during male sex development and SRY directly regulates FGF9/Fgf9 mRNA expression through binding to the SRY-responsive elements in the FGF9/Fgf9 promoter region.